(untitled) (Journal of Biomedical Investigation, 2024)
Background: The ratio of the renal cortical and medullary thicknesses has been reported as a strong indicator of renal function in other populations. Aim: To determine the cortico-medullary ratio (CMR) in selected healthy adults and patients with chronic renal diseases in Aba South Local Government Area, Abia State, Nigeria. Methods: Two-dimensional sonography was conducted to measure the cortical and medullary thicknesses of the kidney parenchyma of 483 participants comprising 405 healthy adults and 78 patients with chronic kidney disease (CKD). The CMR was calculated by dividing cortical thickness by medullary thickness. Blood samples of the participants were collected to determine the serum creatinine and urea levels, while urine samples were checked for the presence of protein. Results: The CMR of healthy adults was 1.27 ± 0.01 for the right kidney and 1.26 ± 0.05 for the left kidney. The mean CMR for the right kidney of healthy participants was 1.27 ± 0.01 while that of CKD patients was 0.93 ± 0.07. The mean CMR for the left kidney of healthy participants was 1.26 ± 0.05 while that of CKD patients was 0.94 ± 0.08. There were significant differences between CMR values of healthy participants and patients with CKD (p<0.05). There was no relationship between CMR and the anthropometric parameters of normal individuals (p>0.05). Conclusion: The mean kidney CMRs for healthy adults and patients with CKD in Aba South have been established. The CMRs in patients with CKD were significantly lower than those of their healthy counterparts suggesting the importance of CMR in sonographic investigation of CKD.